Aluminum-zirconium co-doped cobaltosic oxide positive electrode material as well as preparation method and application thereof
By uniformly doping Zr2+ and Al3+ in lithium cobalt oxide, a co-doped cobalt tetroxide cathode material was prepared, which solved the capacity and circulation performance problems caused by uneven doping in the prior art, and achieved a positive electrode material with high capacity and stable circulation performance.
Patent Information
- Application Number
- CN202411825869.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to achieve uniform doping of Zr2+ and Al3+ in lithium cobalt oxide, resulting in difficult to achieve high capacity and cycle performance stability of the material.
Through specific steps, Al3+ and Zr2+ are uniformly doped into cobalt carbonate, and after calcination and decomposition, they are obtained with uniform particle size and uniform doping elements, and then mixed with the lithium source and heat treatment is performed to prepare aluminum-zirconium co-doped cobalt tetoxide positive electrode material.
It realizes the high capacity and cycling performance stability of aluminum-zirconium co-doped cobalt tetroxide cathode material, and is simple to operate and is suitable for large-scale industrial production.
Smart Images

Figure CN119637946A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a positive electrode material, in particular to an aluminum-zirconium co-doped cobalt oxide positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium cobalt oxide (LCO) cathode material has high specific capacity and compaction density, and is a cathode material with application prospects. In recent years, as people's demand for electronic product functions continues to increase, more components are constantly used inside the products, which seriously squeezes the internal space of lithium-ion batteries. But at the same time, the power demand of products continues to increase, which leads to digital 3C electronic products requiring lithium-ion batteries with higher volume, larger capacity and higher quality energy density.
[0003] At present, some studies have shown that the compaction density can be increased by increasing the particle size of the material, but this alone cannot achieve an increase in the reversible specific capacity of the material. This requires increasing the working voltage of the LCO positive electrode material, which can be achieved by doping with different elements. Many studies have shown that Al 3+ Doping can increase the battery voltage, inhibit the phase change of the layered LCO structure, and effectively improve the thermal stability of the material and enhance the voltage cycle performance. However, if the doping content is too high, it may cause the doping element to replace Co 3+ , resulting in a large capacity loss, while Zr 2+ The doping can make up for the Al 3+ The larger capacity loss caused by the doping amount. However, it is difficult to achieve Zr 2+ With Al 3+ Uniform doping in lithium cobalt oxide.
[0004] Thus, a method is provided to enable Zr 2+ With Al 3+ The preparation method of uniformly doping in lithium cobalt oxide and obtaining aluminum-zirconium co-doped cobalt tetroxide positive electrode material is beneficial to the promotion and application of lithium cobalt oxide positive electrode materials. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide an aluminum-zirconium co-doped cobalt tetroxide positive electrode material and a preparation method and use thereof. The preparation method comprises the following specific steps: 3+ With Zr 2+ It is evenly doped into cobalt carbonate, and after calcination and decomposition, cobalt tetroxide with uniform particle size and uniform doping elements is obtained, which is then mixed with a lithium source and heat treated to obtain an aluminum-zirconium co-doped cobalt tetroxide positive electrode material with high capacity and stable cycle performance.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing an aluminum-zirconium co-doped cobalt oxide positive electrode material, the preparation method comprising the following steps:
[0008] (1) A cobalt-aluminum mixed solution, a zirconium salt solution and a precipitant solution are introduced into the ammonium bicarbonate bottom solution in parallel to prepare aluminum-zirconium co-doped cobalt carbonate by a clarification method.
[0009] (2) The aluminum-zirconium co-doped cobalt carbonate described in step (1) is washed, dried and calcined to obtain an aluminum-zirconium co-doped precursor.
[0010] (3) mixing a lithium source with the aluminum-zirconium co-doped precursor of step (2) to obtain a mixture; subjecting the mixture to a temperature-raising heat treatment and a temperature-insulating heat treatment in sequence to obtain an aluminum-zirconium co-doped cobalt tetroxide positive electrode material; the temperature-raising heat treatment is performed in a protective atmosphere, and the temperature-insulating heat treatment is performed in an oxygen atmosphere.
[0011] In the aluminum-zirconium co-doped cobalt tetroxide positive electrode material, the doping amount of aluminum is 9000ppm-11000ppm, and the doping amount of zirconium is 700ppm-2000ppm.
[0012] The preparation method provided by the present invention uses ammonium bicarbonate as a complexing agent and a precipitating agent, and through specific steps, Al 3+ With Zr 2+ It is evenly doped into cobalt carbonate, and after calcination and decomposition, cobalt tetroxide with uniform particle size and uniform doping elements is obtained, which is then mixed with a lithium source and heat treated to obtain an aluminum-zirconium co-doped cobalt tetroxide positive electrode material with high capacity and stable cycle performance.
[0013] Preferably, the clarification method in step (1) includes a nucleation stage and a growth stage; the pH value of the nucleation stage is 7.3-8.4; and the pH value of the growth stage is 6.9-7.0.
[0014] Preferably, the preparation temperature of the clarification method in step (1) is 42°C-45°C.
[0015] Preferably, the preparation process by the clarification method is accompanied by stirring at a speed of 60 r / min-230 r / min.
[0016] Preferably, the shutdown particle size D50 prepared by the clarification method is 13 μm-18 μm.
[0017] Preferably, the pH value of the ammonium bicarbonate base solution in step (1) is 7.4-8.6.
[0018] Preferably, the cobalt ion concentration in the cobalt-aluminum mixed solution in step (1) is 110 g / L-130 g / L.
[0019] Preferably, the zirconium ion concentration in the zirconium salt solution in step (1) is 0.5 g / L-15 g / L.
[0020] Preferably, the precipitant in the precipitant solution in step (1) comprises any one of sodium bicarbonate, sodium hydroxide or sodium carbonate, or a combination of at least two of them.
[0021] Preferably, the washing in step (2) is performed using an ammonium bicarbonate solution with a concentration of 30 g / L-50 g / L.
[0022] Preferably, the drying temperature in step (2) is 100°C-150°C.
[0023] Preferably, the heating rate of the calcination in step (2) is 8°C / min-12°C / min.
[0024] Preferably, the calcination temperature in step (2) is 500°C-780°C.
[0025] Preferably, the calcination holding time in step (2) is 60 min-210 min.
[0026] Preferably, the heating rate of the heating treatment in step (3) is 7°C / min-10°C / min.
[0027] Preferably, the heating end point temperature of the heating treatment in step (3) is 700°C-1000°C.
[0028] Preferably, the temperature of the heat preservation heat treatment in step (3) is equal to the heating end point temperature of the heating heat treatment.
[0029] Preferably, the insulation time of the insulation heat treatment in step (3) is 10h-20h.
[0030] In a second aspect, the present invention provides an aluminum-zirconium co-doped cobalt oxide positive electrode material, wherein the aluminum-zirconium co-doped cobalt oxide positive electrode material is prepared by the preparation method described in the first aspect.
[0031] In a third aspect, the present invention provides a positive electrode, comprising a current collector and a positive electrode active material disposed on at least one side of the current collector; the positive electrode active material comprises the aluminum-zirconium co-doped cobalt oxide positive electrode material described in the second aspect.
[0032] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The preparation method provided by the present invention comprises the following specific steps: 3+ With Zr 2+ It is uniformly doped into cobalt carbonate, and after calcination and decomposition, cobalt tetroxide with uniform particle size and uniform doping elements is obtained, which is then mixed with a lithium source and subjected to heat treatment to obtain an aluminum-zirconium co-doped cobalt tetroxide positive electrode material with high capacity and stable cycle performance; moreover, the preparation method provided by the present invention is simple to operate and is suitable for industrial large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a SEM image of the aluminum-zirconium co-doped cobalt oxide positive electrode material obtained in Example 1 of the present invention.
[0036] Figure 2 and Figure 3 This is the EDS image of the aluminum-zirconium co-doped cobalt oxide positive electrode material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0038] A certain embodiment of the present invention provides a method for preparing an aluminum-zirconium co-doped cobalt oxide positive electrode material, the preparation method comprising the following steps:
[0039] (1) A cobalt-aluminum mixed solution, a zirconium salt solution and a precipitant solution are introduced into the ammonium bicarbonate bottom solution in parallel to prepare aluminum-zirconium co-doped cobalt carbonate by a clarification method.
[0040] (2) The aluminum-zirconium co-doped cobalt carbonate described in step (1) is washed, dried and calcined to obtain an aluminum-zirconium co-doped precursor.
[0041] (3) mixing a lithium source with the aluminum-zirconium co-doped precursor of step (2) to obtain a mixture; subjecting the mixture to a temperature-raising heat treatment and a temperature-insulating heat treatment in sequence to obtain an aluminum-zirconium co-doped cobalt tetroxide positive electrode material; the temperature-raising heat treatment is performed in a protective atmosphere, and the temperature-insulating heat treatment is performed in an oxygen atmosphere.
[0042] In the aluminum-zirconium co-doped cobalt tetroxide positive electrode material, the doping amount of aluminum is 9000ppm-11000ppm, and the doping amount of zirconium is 700ppm-2000ppm.
[0043] The preparation method provided by the present invention comprises the following specific steps: 3+ With Zr 2+It is evenly doped into cobalt carbonate, and after calcination and decomposition, cobalt tetroxide with uniform particle size and uniform doping elements is obtained, which is then mixed with a lithium source and heat treated to obtain an aluminum-zirconium co-doped cobalt tetroxide positive electrode material with high capacity and stable cycle performance.
[0044] In the preparation method provided by the present invention, by adjusting the concentration and flow rate of the cobalt-aluminum mixed solution and the zirconium salt solution, the doping amounts of aluminum and zirconium in the final aluminum-zirconium co-doped cobalt tetroxide positive electrode material meet the process requirements, wherein the doping amount of aluminum is 9000ppm-11000ppm, for example, it can be 9000ppm, 9500ppm, 10000ppm, 10500ppm or 11000ppm; the doping amount of zirconium is 700ppm-2000ppm, for example, it can be 700ppm, 1000ppm, 1200ppm, 1500ppm, 1800ppm or 2000ppm.
[0045] The aluminum doping amount in the present invention refers to the mass ratio of aluminum to the aluminum-zirconium co-doped cobalt tetroxide positive electrode material; the zirconium doping amount refers to the mass ratio of zirconium to the aluminum-zirconium co-doped cobalt tetroxide positive electrode material.
[0046] The clarification method in the present invention refers to: firstly, a certain volume percentage of ammonium bicarbonate bottom liquid is introduced into the reactor, and then under certain temperature conditions and stirring conditions, a cobalt aluminum mixed liquid, a zirconium salt solution and a precipitant solution are introduced into the ammonium bicarbonate bottom liquid, and when the volume of the cobalt aluminum mixed liquid introduced reaches a certain value, the stirring and the introduction of the materials are stopped, and after the liquid surface is allowed to stand for stratification, the supernatant is extracted; then the stirring is turned on and the materials are continued to be introduced for reaction. During the reaction process, as more and more crystal seeds are in the reactor, a split reactor operation is required when the particle size of the material reacts to a certain size.
[0047] In certain embodiments, the clarification method in step (1) includes a nucleation stage and a growth stage; the pH value of the nucleation stage is 7.3-8.4; and the pH value of the growth stage is 6.9-7.0.
[0048] The nucleation stage in the present invention refers to the initial stage of the formation of aluminum-zirconium co-doped cobalt carbonate, in which the metal salt and the complexing agent ammonium bicarbonate spontaneously generate crystal nuclei in the bottom liquid. During the growth stage in the present invention, the primary particles form spherical secondary particles through agglomeration, secondary growth, and secondary outward extension.
[0049] The pH value of the nucleation stage is 7.3-8.4, for example, 7.3, 7.5, 7.8, 8, 8.2 or 8.4, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0050] The pH value in the growth stage is 6.9-7.0, for example, 6.9 or 7.0, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0051] In the present invention, the pH value in the nucleation stage and the pH value in the growth stage are controlled by the inflow rate and / or concentration of the precipitant solution.
[0052] In certain embodiments, the preparation temperature of the clarification method in step (1) is 42°C-45°C, for example, 42°C, 43°C, 44°C or 45°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0053] In certain embodiments, the clarification method is accompanied by stirring at a speed of 60 r / min-230 r / min, for example, 60 r / min, 100 r / min, 120 r / min, 150 r / min, 180 r / min, 200 r / min or 230 r / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0054] In some embodiments, the shutdown particle size D50 prepared by the clarification method is 13 μm-18 μm, for example, it can be 13 μm, 14 μm, 15 μm, 16 μm or 18 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In certain embodiments, in order to achieve the shutdown particle size, during the clarification process, the separation operation includes separation when the particle size D50 reaches 6 μm-7 μm and 9 μm-11 μm respectively.
[0056] In certain embodiments, the pH value of the ammonium bicarbonate base solution in step (1) is 7.4-8.6, for example, 7.4, 7.5, 7.6, 7.8, 8, 8.2, 8.5 or 8.6, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0057] In certain embodiments, the cobalt ion concentration in the cobalt-aluminum mixed solution in step (1) is 110 g / L-130 g / L, for example, it can be 110 g / L, 115 g / L, 120 g / L, 125 g / L or 130 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0058] In certain embodiments, the cobalt salt in the cobalt-aluminum mixed solution of step (1) is any one of cobalt nitrate, cobalt acetate or cobalt chloride, or a combination of at least two of them. Typical but non-limiting combinations include a combination of cobalt acetate and cobalt acetate, a combination of cobalt acetate and cobalt chloride, a combination of cobalt nitrate and cobalt chloride, or a combination of cobalt nitrate, cobalt acetate and cobalt chloride.
[0059] In certain embodiments, the aluminum salt in the cobalt-aluminum mixed solution in step (1) includes any one of aluminum nitrate, aluminum sulfate or aluminum chloride, or a combination of at least two of them. Typical but non-limiting combinations include a combination of aluminum nitrate and aluminum sulfate, a combination of aluminum sulfate and aluminum chloride, a combination of aluminum nitrate and aluminum chloride, or a combination of aluminum nitrate, aluminum sulfate and aluminum chloride.
[0060] The present invention does not limit the aluminum ion concentration in the cobalt-aluminum mixed solution, as long as the aluminum-zirconium co-doped cobalt tetroxide positive electrode material has an aluminum doping amount of 9000ppm-11000ppm and a zirconium doping amount of 700ppm-2000ppm.
[0061] In certain embodiments, the zirconium ion concentration in the zirconium salt solution in step (1) is 0.5 g / L-15 g / L, for example, 0.5 g / L, 1 g / L, 3 g / L, 5 g / L, 8 g / L, 10 g / L, 12 g / L or 15 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0062] Optionally, the zirconium salt in the zirconium salt solution in step (1) includes any one of zirconium nitrate, zirconium sulfate or zirconium acetate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of zirconium nitrate and zirconium sulfate, a combination of zirconium sulfate and zirconium acetate, a combination of zirconium nitrate and zirconium acetate, or a combination of zirconium nitrate, zirconium sulfate and zirconium acetate.
[0063] In certain embodiments, the precipitant in the precipitant solution of step (1) comprises any one of sodium bicarbonate, sodium hydroxide or sodium carbonate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of ammonium bicarbonate and sodium hydroxide, a combination of sodium hydroxide and sodium carbonate, a combination of sodium carbonate and ammonium bicarbonate, or a combination of sodium bicarbonate, sodium hydroxide and sodium carbonate.
[0064] The present invention does not specifically limit the concentration of the precipitant solution, and its flow rate and concentration can be adjusted according to the pH value required in the reaction stage.
[0065] In certain embodiments, during the clarification method preparation process in step (1), the absolute pressure is 0.3 MPa-0.6 MPa, for example, it can be 0.3 MPa, 0.4 MPa, 0.5 MPa or 0.6 MPa, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0066] In certain embodiments, the washing in step (2) is performed using an ammonium bicarbonate solution having a concentration of 30 g / L-50 g / L, for example, 30 g / L, 35 g / L, 40 g / L, 45 g / L or 50 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0067] In certain embodiments, the drying temperature in step (2) is 100°C-150°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0068] In certain embodiments, the heating rate of the calcination in step (2) is 8°C / min-12°C / min, for example, 8°C / min, 9°C / min, 10°C / min, 11°C / min or 12°C / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0069] In certain embodiments, the calcination temperature in step (2) is 500°C-780°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 780°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0070] In some embodiments, the holding time of the calcination in step (2) is 60 min-210 min, for example, 60 min, 100 min, 150 min, 200 min or 210 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0071] In certain embodiments, the calcination in step (2) is performed in a rotary kiln or an atmosphere furnace.
[0072] In some embodiments, the heating rate of the temperature-raising heat treatment in step (3) is 7°C / min-10°C / min, for example, 7, 8, 9 or 10, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0073] In some embodiments, the final temperature of the heating heat treatment in step (3) is 700°C-1000°C, for example, it can be 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0074] In some embodiments, the temperature of the heat preservation heat treatment in step (3) is equal to the heating end point temperature of the heating heat treatment.
[0075] In some embodiments, the insulation time of the insulation heat treatment in step (3) is 10h-20h, for example, it can be 10h, 12h, 15h, 18h or 20h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] A certain embodiment of the present invention provides an aluminum-zirconium co-doped cobalt oxide positive electrode material, and the aluminum-zirconium co-doped cobalt oxide positive electrode material is prepared by the preparation method described in any embodiment.
[0077] The present invention provides a positive electrode, which comprises a current collector and a positive electrode active material arranged on at least one side of the current collector; the positive electrode active material comprises the aluminum-zirconium co-doped cobalt tetroxide positive electrode material described in any embodiment.
[0078] Example 1
[0079] This embodiment provides a method for preparing an aluminum-zirconium co-doped cobalt oxide positive electrode material, the preparation method comprising the following steps:
[0080] (1) Add ammonium bicarbonate bottom liquid into a 50 L reactor with a nitrogen atmosphere and an absolute pressure of 0.3 MPa; the volume proportion of the ammonium bicarbonate bottom liquid in the reactor is 40%, and the pH value is 7.4.
[0081] (2) Under the conditions of a temperature of 45°C and a stirring speed of 230 r / min, a cobalt-aluminum mixed solution (cobalt nitrate and aluminum nitrate, with a cobalt ion concentration of 120 g / L and a flow rate of 15 L / h), a zirconium salt solution (zirconium nitrate, with a zirconium ion concentration of 5 g / L) and a precipitant solution (ammonium bicarbonate solution) were introduced into the ammonium bicarbonate bottom liquid in parallel to prepare aluminum-zirconium co-doped cobalt carbonate by a clarification method; the clarification method preparation process includes a nucleation stage and a growth stage, the pH value of the nucleation stage is 8, the pH value of the growth stage is 6.9, the particle sizes of the separate kettles are 6.5 μm and 10 μm, respectively, and the shutdown particle size is 16 μm.
[0082] (3) The aluminum-zirconium co-doped cobalt carbonate is washed with an ammonium bicarbonate solution with a concentration of 40 g / L, then dried at a temperature of 120°C, and then calcined and decomposed to obtain an aluminum-zirconium co-doped precursor; the calcination and decomposition are carried out in a rotary kiln with a heating rate of 10°C / min, a temperature of 600°C, and a holding time of 150 min.
[0083] (4) An aluminum-zirconium co-doped precursor is mixed with Li2CO3 at a molar ratio of cobalt to lithium of 1:1.3 to obtain a mixture; the obtained mixture is subjected to a heating heat treatment and a heat preservation heat treatment in sequence, and is crushed and screened to remove iron, to obtain an aluminum-zirconium co-doped cobalt tetroxide positive electrode material (the doping amount of aluminum is 10000 ppm, and the doping amount of zirconium is 1500 ppm); the heating heat treatment is carried out in a nitrogen atmosphere, and the heat preservation heat treatment is carried out in an oxygen atmosphere; the heating rate of the heating heat treatment is 8°C / min, the heating end temperature is 850°C, and the heat preservation time is 13h.
[0084] The SEM image of the aluminum-zirconium co-doped cobalt tetroxide positive electrode material obtained in this example is as follows Figure 1 As shown, the EDS diagram of Al element distribution is as follows Figure 2 As shown, the EDS diagram of Zr element distribution is as follows Figure 3 As shown by Figure 1 , Figure 2 and Figure 3 It can be seen that the preparation method provided in this embodiment can obtain an aluminum-zirconium co-doped cobalt oxide positive electrode material with uniform particle size and uniform distribution of aluminum and zirconium.
[0085] Example 2
[0086] This embodiment provides a method for preparing an aluminum-zirconium co-doped cobalt oxide positive electrode material, the preparation method comprising the following steps:
[0087] (1) Add ammonium bicarbonate bottom liquid into a 50 L reactor with a nitrogen atmosphere and an absolute pressure of 0.5 MPa; the volume proportion of the ammonium bicarbonate bottom liquid in the reactor is 40%, and the pH value is 8.
[0088] (2) Under the conditions of a temperature of 43°C and a stirring speed of 150 r / min, a cobalt-aluminum mixed solution (cobalt nitrate and aluminum nitrate, with a cobalt ion concentration of 110 g / L and a flow rate of 9 L / h), a zirconium salt solution (zirconium nitrate, with a zirconium ion concentration of 0.5 g / L) and a precipitant solution (ammonium bicarbonate solution) were simultaneously introduced into the ammonium bicarbonate bottom liquid to prepare aluminum-zirconium co-doped cobalt carbonate by a clarification method; the clarification method preparation process includes a nucleation stage and a growth stage, the pH value of the nucleation stage is 7.3, the pH value of the growth stage is 6.9, the particle sizes of the separate kettles are 6 μm and 9 μm, respectively, and the shutdown particle size is 13 μm.
[0089] (3) The aluminum-zirconium co-doped cobalt carbonate is washed with an ammonium bicarbonate solution with a concentration of 30 g / L, then dried at a temperature of 100°C, and then calcined and decomposed to obtain an aluminum-zirconium co-doped precursor; the calcination and decomposition are carried out in a rotary kiln with a heating rate of 8°C / min, a temperature of 500°C, and a holding time of 210 min.
[0090] (4) An aluminum-zirconium co-doped precursor is mixed with Li2CO3 at a molar ratio of cobalt element to lithium element of 1:1.3 to obtain a mixture; the obtained mixture is subjected to a heating heat treatment and a heat preservation heat treatment in sequence, and is crushed and screened to remove iron, to obtain an aluminum-zirconium co-doped cobalt tetroxide positive electrode material (the doping amount of aluminum is 9000ppm, and the doping amount of zirconium is 700ppm); the heating heat treatment is carried out in a nitrogen atmosphere, and the heat preservation heat treatment is carried out in an oxygen atmosphere; the heating rate of the heating heat treatment is 7°C / min, the heating end temperature is 700°C, and the insulation time is 20h.
[0091] Example 3
[0092] This embodiment provides a method for preparing an aluminum-zirconium co-doped cobalt oxide positive electrode material, the preparation method comprising the following steps:
[0093] (1) Add ammonium bicarbonate bottom liquid into a 50 L reactor with a nitrogen atmosphere and an absolute pressure of 0.6 MPa; the volume proportion of the ammonium bicarbonate bottom liquid in the reactor is 40%, and the pH value is 8.6.
[0094] (2) Under the conditions of a temperature of 42°C and a stirring speed of 60 r / min, a cobalt-aluminum mixed solution (cobalt nitrate and aluminum nitrate, with a cobalt ion concentration of 130 g / L and a flow rate of 9 L / h), a zirconium salt solution (zirconium nitrate, with a zirconium ion concentration of 15 g / L) and a precipitant solution (ammonium bicarbonate solution) were simultaneously introduced into the ammonium bicarbonate bottom liquid to prepare aluminum-zirconium co-doped cobalt carbonate by a clarification method; the clarification method preparation process includes a nucleation stage and a growth stage, the pH value of the nucleation stage is 8.4, the pH value of the growth stage is 7.0, the particle sizes of the separate kettles are 7 μm and 11 μm, respectively, and the shutdown particle size is 18 μm.
[0095] (3) The aluminum-zirconium co-doped cobalt carbonate is washed with an ammonium bicarbonate solution with a concentration of 50 g / L, then dried at a temperature of 150°C, and then calcined and decomposed to obtain an aluminum-zirconium co-doped precursor; the calcination and decomposition are carried out in a rotary kiln with a heating rate of 12°C / min, a temperature of 780°C, and a holding time of 60 min.
[0096] (4) An aluminum-zirconium co-doped precursor is mixed with Li2CO3 at a molar ratio of cobalt to lithium of 1:1.3 to obtain a mixture; the obtained mixture is subjected to a heating heat treatment and a heat preservation heat treatment in sequence, and is crushed and screened to remove iron, to obtain an aluminum-zirconium co-doped cobalt tetroxide positive electrode material (the doping amount of aluminum is 11000 ppm, and the doping amount of zirconium is 2000 ppm); the heating heat treatment is carried out in a nitrogen atmosphere, and the heat preservation heat treatment is carried out in an oxygen atmosphere; the heating rate of the heating heat treatment is 10°C / min, the heating end temperature is 1000°C, and the heat preservation time is 10h.
[0097] Comparative Example 1
[0098] This comparative example provides a method for preparing an aluminum-zirconium co-doped cobalt oxide positive electrode material, which is the same as Example 1 except that the temperature-raising heat treatment and the heat-insulating heat treatment are both performed in a nitrogen atmosphere.
[0099] Comparative Example 2
[0100] This comparative example provides a method for preparing an aluminum-zirconium co-doped cobalt oxide positive electrode material, which is the same as Example 1 except that the temperature-raising heat treatment and the heat-insulating heat treatment are both performed in an oxygen atmosphere.
[0101] Comparative Example 3
[0102] This comparative example provides a method for preparing an aluminum-zirconium co-doped cobalt tetroxide positive electrode material, which is the same as Example 1 except that the aluminum salt concentration in the cobalt-aluminum mixed solution is changed so that the aluminum doping amount in the aluminum-zirconium co-doped cobalt tetroxide positive electrode material is 8000 ppm.
[0103] Comparative Example 4
[0104] This comparative example provides a method for preparing an aluminum-zirconium co-doped cobalt tetroxide positive electrode material, which is the same as Example 1 except that the aluminum salt concentration in the cobalt-aluminum mixed solution is changed so that the aluminum doping amount in the aluminum-zirconium co-doped cobalt tetroxide positive electrode material is 12000 ppm.
[0105] Comparative Example 5
[0106] This comparative example provides a method for preparing an aluminum-zirconium co-doped cobalt oxide positive electrode material, which is the same as Example 1 except that the zirconium salt concentration of the zirconium salt solution is changed so that the zirconium doping amount in the aluminum-zirconium co-doped cobalt oxide positive electrode material is 500 ppm.
[0107] Comparative Example 6
[0108] This comparative example provides a method for preparing an aluminum-zirconium co-doped cobalt oxide positive electrode material, which is the same as Example 1 except that the zirconium salt concentration of the zirconium salt solution is changed so that the zirconium doping amount in the aluminum-zirconium co-doped cobalt oxide positive electrode material is 2400 ppm.
[0109] Comparative Example 7
[0110] This comparative example provides a method for preparing an aluminum-zirconium co-doped cobalt oxide positive electrode material, the preparation method comprising the following steps:
[0111] (1) Add ammonium bicarbonate bottom liquid into a 50 L reactor with a nitrogen atmosphere and an absolute pressure of 0.3 MPa; the volume proportion of the ammonium bicarbonate bottom liquid in the reactor is 40%, and the pH value is 7.4.
[0112] (2) Under the conditions of a temperature of 45°C and a stirring speed of 230 r / min, a cobalt salt solution (cobalt nitrate, cobalt ion concentration of 120 g / L, flow rate of 15 L / h), an aluminum salt solution (aluminum nitrate, aluminum ion concentration of 10 g / L), a zirconium salt solution (zirconium nitrate, zirconium ion concentration of 5 g / L) and a precipitant solution (ammonium bicarbonate solution) were introduced into the ammonium bicarbonate bottom liquid in parallel to prepare aluminum-zirconium co-doped cobalt carbonate by a clarification method; the clarification method preparation process includes a nucleation stage and a growth stage, the pH value of the nucleation stage is 8, the pH value of the growth stage is 6.9, the particle sizes of the separate kettles are 6.5 μm and 10 μm, respectively, and the shutdown particle size is 16 μm.
[0113] (3) The aluminum-zirconium co-doped cobalt carbonate is washed with an ammonium bicarbonate solution with a concentration of 40 g / L, then dried at a temperature of 120°C, and then calcined and decomposed to obtain an aluminum-zirconium co-doped precursor; the calcination and decomposition are carried out in a rotary kiln with a heating rate of 10°C / min, a temperature of 600°C, and a holding time of 150 min.
[0114] (4) An aluminum-zirconium co-doped precursor is mixed with Li2CO3 at a molar ratio of cobalt to lithium of 1:1.3 to obtain a mixture; the obtained mixture is subjected to a heating heat treatment and a heat preservation heat treatment in sequence, and is crushed and screened to remove iron, to obtain an aluminum-zirconium co-doped cobalt tetroxide positive electrode material (the doping amount of aluminum is 10000 ppm, and the doping amount of zirconium is 1500 ppm); the heating heat treatment is carried out in a nitrogen atmosphere, and the heat preservation heat treatment is carried out in an oxygen atmosphere; the heating rate of the heating heat treatment is 8°C / min, the heating end temperature is 850°C, and the heat preservation time is 13h.
[0115] Performance Characterization
[0116] The aluminum-zirconium co-doped cobalt oxide positive electrode material obtained in the above embodiments and comparative examples was characterized: the aluminum-zirconium co-doped cobalt oxide positive electrode material, carbon black, polyvinylidene fluoride and N-methylpyrrolidone were mixed into a slurry in a mass ratio of 8:1:1:4, coated on aluminum foil, vacuum dried at 105°C for 2h, and then put into a tablet press for compacting at a pressure of 25MPa, and cut to obtain a positive electrode; a lithium sheet was used as a negative electrode; the electrolyte was a solute, a solvent and an additive in a mass ratio of 10:85:5, the solvent was ethylene carbonate, diethyl carbonate and dimethyl carbonate in a volume ratio of 1:1:1, the solute was lithium hexafluorophosphate, and the additive was fluoroethylene carbonate; the diaphragm was a polyethylene film; button battery 2032 was assembled for charge and discharge tests, the test voltage was 3V-4.4V, and the first discharge specific capacity at a rate of 0.1C and the cycle capacity retention rate after 500 charge and discharge cycles at a rate of 0.1C were recorded, and the results are shown in Table 1.
[0117] Table 1
[0118]
[0119] In summary, the preparation method provided by the present invention comprises the following specific steps: 3+ With Zr 2+ It is evenly doped into cobalt carbonate, and after calcination and decomposition, cobalt tetroxide with uniform particle size and uniform doping elements is obtained, which is then mixed with a lithium source and heat treated to obtain an aluminum-zirconium co-doped cobalt tetroxide positive electrode material with high capacity and stable cycle performance.
[0120] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing an aluminum-zirconium co-doped cobalt oxide positive electrode material, characterized in that: The preparation method comprises the following steps: (1) a cobalt-aluminum mixed solution, a zirconium salt solution and a precipitant solution are introduced into the ammonium bicarbonate bottom solution in parallel to prepare aluminum-zirconium co-doped cobalt carbonate by a clarification method; (2) The aluminum-zirconium co-doped cobalt carbonate in step (1) is washed, dried and calcined to obtain an aluminum-zirconium co-doped precursor; (3) mixing a lithium source with the aluminum-zirconium co-doped precursor of step (2) to obtain a mixture; the mixture is subjected to a temperature-raising heat treatment and a temperature-insulating heat treatment in sequence to obtain an aluminum-zirconium co-doped cobalt oxide positive electrode material; the temperature-raising heat treatment is performed in a protective atmosphere, and the temperature-insulating heat treatment is performed in an oxygen atmosphere; In the aluminum-zirconium co-doped cobalt tetroxide positive electrode material, the doping amount of aluminum is 9000ppm-11000ppm, and the doping amount of zirconium is 700ppm-2000ppm.
2. The preparation method according to claim 1, characterized in that: The clarification method in step (1) includes a nucleation stage and a growth stage; The pH value of the nucleation stage is 7.3-8.4; The pH value during the growth phase is 6.9-7.
0.
3. The preparation method according to claim 1, characterized in that: The preparation temperature of the clarification method in step (1) is 42° C.-45° C.; And / or, the clarification method is accompanied by stirring at a speed of 60 r / min-230 r / min; And / or, the shutdown particle size D50 prepared by the clarification method is 13 μm-18 μm.
4. The preparation method according to claim 1, characterized in that: The pH value of the ammonium bicarbonate base solution in step (1) is 7.4-8.6; And / or, the cobalt ion concentration in the cobalt-aluminum mixed solution in step (1) is 110 g / L-130 g / L; And / or, the zirconium ion concentration in the zirconium salt solution in step (1) is 0.5 g / L-15 g / L; And / or, the precipitant in the precipitant solution in step (1) includes any one of sodium bicarbonate, sodium hydroxide or sodium carbonate, or a combination of at least two of them.
5. The preparation method according to claim 1, characterized in that: The washing in step (2) is performed by using an ammonium bicarbonate solution with a concentration of 30 g / L-50 g / L.
6. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 100°C-150°C.
7. The preparation method according to claim 1, characterized in that: The heating rate of the calcination in step (2) is 8°C / min-12°C / min; And / or, the calcination temperature in step (2) is 500° C.-780° C.; And / or, the calcination holding time in step (2) is 60 min-210 min.
8. The preparation method according to claim 1, characterized in that: The heating rate of the heating treatment in step (3) is 7°C / min-10°C / min; And / or, the heating end point temperature of the heating treatment in step (3) is 700° C.-1000° C.; And / or, the temperature of the heat preservation heat treatment in step (3) is equal to the heating end point temperature of the heating heat treatment; And / or, the insulation time of the insulation heat treatment in step (3) is 10h-20h.
9. An aluminum-zirconium co-doped cobalt oxide positive electrode material, characterized in that: The aluminum-zirconium co-doped cobalt oxide positive electrode material is prepared by the preparation method according to any one of claims 1 to 8.
10. A positive electrode, characterized in that: The positive electrode comprises a current collector and a positive electrode active material disposed on at least one side of the current collector; The positive electrode active material comprises the aluminum-zirconium co-doped cobalt oxide positive electrode material according to claim 9.
Citation Information
Cited By
High-aluminum-doped cobaltosic oxide precursor and preparation method and application thereof
CN120903573A